Associations between dietary and supplemental vitamin A intake and melanoma and non‐melanoma skin cancer - Vaishali Mittal; Jodi Y. So; Shufeng Li; Susan M. Swetter; Eleni Linos; Linda VanHorn; Marian L. Neuhouser; Marcia L. Stefanick; Jean Y. Tang (Skin Health and Disease)
Abstract Background Cutaneous melanoma (CM) and non‐melanoma skin cancer (NMSC) are rising in postmenopausal women. Although high doses of oral vitamin A reduce NMSC risk in high‐risk patients, the role of vitamin A in preventing skin cancer in this group remains unexplored. Objectives To determine the association between total (dietary and supplemental) vitamin A and risk of CM and NMSC in postmenopausal women. Methods This retrospective cohort study included 52 877 White women from the Women's Health Initiative cohort, spanning from 1993 to 2019. Exposures were intake of total vitamin A, retinol and provitamin A carotenoids. Cox proportional hazard models estimated hazard ratios for overall CM incidence, whereas logistic regression determined odds ratios (ORs) for melanoma subtypes and NMSC. Results 1154 cases of CM and 9085 cases of NMSC were identified over an average follow‐up period of 17.8 years (SD 6.7). No associations were identified between total vitamin A intake and melanoma risk. Higher dietary vitamin A intake was associated with higher risk of NMSC (OR of 3rd vs. 1st tertile of dietary intake = 1.12, 95% confidence interval [CI] [1.06, 1.18]), as was dietary beta‐cryptoxanthin, a provitamin A carotenoid (OR of 3rd vs. 1st tertile of dietary intake = 1.22, 95% CI [1.15, 1.29]); these results were consistent across both age‐ and fully adjusted regression models. Conclusions Total vitamin A intake was not associated with lower risk of CM or NMSC. Dietary vitamin A and beta‐cryptoxanthin intake were associated with a slightly higher risk of NMSC in postmenopausal women.